The outcome of loose bone fragments in pediatric supracondylar humerus fractures: a retrospective study. Issue 1 (9th December 2020) - Yang, Lei; Yang, Panyi; Li, Lang; Tang, Xueyang
Abstract : We evaluated the clinical and imaging outcomes of loose bone fragments in children with supracondylar humerus fractures after closed reduction with percutaneous pin (CRPP) fixation. A retrospective review was conducted on 12 children with fragments on imaging after closed reduction of displaced humeral supracondylar fractures (Gartland III). Primary radiographic assessment included fragment outcome, postoperative Baumann angle, carrying angle and loss of reduction. Clinical outcome included the elbow range of motion (ROM), Flynn grade and other complications. Between January 2015 and January 2018, 460 children (2–14 years old) with supracondylar humerus fractures were treated at our center, including 12 (2.6%) with loose bone fragments on postoperative X-ray. Union or absorption of fragments was noted in all 12 patients at 1 year postoperatively, with good radiographic and clinical outcomes. The mean Baumann angle was 15.5° ± 4.3° and the mean carrying angle was 11.2° ± 2.8°. All patients had a normal elbow ROM. Ten patients achieved an excellent and two a good result according to the Flynn criteria. Good results were achieved after CRPP fixation in 12 children with supracondylar humerus fractures and loose bone fragments. The fragments were mainly absorbed or achieved union to the humerus within 1 year.